2013
DOI: 10.1371/journal.pgen.1003923
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Unraveling of the Unsolved Pathway of Nicotine Degradation in Pseudomonas

Abstract: Microorganisms such as Pseudomonas putida play important roles in the mineralization of organic wastes and toxic compounds. To comprehensively and accurately elucidate key processes of nicotine degradation in Pseudomonas putida, we measured differential protein abundance levels with MS-based spectral counting in P. putida S16 grown on nicotine or glycerol, a non-repressive carbon source. In silico analyses highlighted significant clustering of proteins involved in a functional pathway in nicotine degradation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
156
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 30 publications
(52 reference statements)
2
156
0
Order By: Relevance
“…The biotransformation of 6HN to 6HMM and 6HPON was confirmed by using 6HN as the substrate; HSP was transformed to form 2,5-DHP, and 2,5-DHP could be further converted (data not shown). However, SP could not be transformed by resting cells of strain SJY1, which confirmed that HSP was not transformed from SP as in the pyrrolidine pathway (13). No blue pigment was produced during nicotine degradation, indicating that 6HPON was not transformed into 2,3,6-trihydroxypyridine.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…The biotransformation of 6HN to 6HMM and 6HPON was confirmed by using 6HN as the substrate; HSP was transformed to form 2,5-DHP, and 2,5-DHP could be further converted (data not shown). However, SP could not be transformed by resting cells of strain SJY1, which confirmed that HSP was not transformed from SP as in the pyrrolidine pathway (13). No blue pigment was produced during nicotine degradation, indicating that 6HPON was not transformed into 2,3,6-trihydroxypyridine.…”
mentioning
confidence: 78%
“…2,5-DHP is a central metabolic intermediate in the catabolism of many pyridine derivatives (23,30). Genome sequencing promotes the study of molecular mechanisms of xenobiotic degradation (13,22), because genes can be identified through sequence alignment with isoenzymes or enzymes with similar functions. Genes responsible for the conversion of nicotine to 6HN and for the conversion from 6HPON to HSP have still not been found in the genome of strain SJY1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations